(untitled) (Cadernos de Sociomuseologia, 2022)
This paper presents the NATAL DESENHADA extension project, a partnership between DARQ/UFRN and the USK Natal group. Such project seeks to foster discussions on cultural heritage through actions that articulate heritage education activities with drawing on location practices, starting from two premises: an extended approach to the concept of cultural heritage, in which everyday life is treated as a base; and the understanding that heritage education takes place in broad cultural contexts in which the school is not the only educational agent. By emphasizing the need to broaden the concept of cultural heritage and the incorporation of everyday practice as a fundamental element in this discussion, we consider addressing access and inclusive practices as fundamental aspects for the discussion. In 2018 and 2019, the activities took place in person, in the neighbourhoods of Ribeira and Cidade Alta, and aimed to build nexuses between generations that did not know these neighbourhoods in a pulsating and lively way. In 2020 and 2021 the project held online meetings due to the COVID19 pandemic. During 2020, activities pointed to the diversity of uses, memories, affection and difficulties in valuing cultural heritage in the Alecrim neighbourhood. In 2021, virtual activities happened in small towns around the state and in the Natal metropolitan region. In 2022, the face-to-face format was resumed, in neighbourhoods in the north of the city, having high school communities as target audiences. We reinforce the importance of extension actions in bringing academic knowledge closer to the daily life of cities, incorporating it into the spectrum of cultural heritage. We emphasize that the adaptation to the remote mode, with the adoption of digital resources, does not replace the experience of the body in the city. Keywords: Cultural Heritage; drawing; everyday life; Urban Sketchers Natal (Brazil)